Legal Regulation of Expressing Opinions and Beliefs in Print Mass Media - S. A. Kucher (Bulletin of Kharkiv National University of Internal Affairs)
The research is focused on the problems of legal regulation of expressing opinions and beliefs in print media. The scientific novelty of the research constitutes propositions on supplementing the Law of Ukraine “On Print Mass Media (Press) in Ukraine” with a new norm that would regulate the work of electronic pages of the print media.